Shah Abbas’s Relationship with the Larestan Miladi Dynasty Rulers (Review of the Collapse of the Lar Dynasty, the Oldest Iranian Local State) - Mohajer, Mohammad Baqer; Jamali, Mohammad Kariem Yousef; Jadidi, Naser (Journal of History Culture and Art Research, 2017)
The Larestan Miladi family dynasty is considered to be the oldest local state in Iran's history, governing more than sixteen centuries in large parts of the southern Fars province. According to the local narratives, the history of this state dates back to the first half of the 1st century AD with the reign of Goodarz Parthian. The children and dependents of Gorgin Milad, the founder of Larestan Miladi Dynasty ruled over the region for long due to the particular geographic and weather conditions of the region that made it ousted from socio-political events. Having declared loyalty, they were able to continue their semi-independent rule until the beginning of the reign of Shah Abbas I (996-1038 AH), with the advent of the Safavid dynasty and the centralizationist policies of this dynasty. However, the disagreement between Ibrahim Khan’s, the latest Lar Miladi Dynasty ruler, and the Provincial Government of Fars and the central government of Safavid in the Shah Abbas I , eventually led to the invasion of Allahverdykhan , the Governor of Fars to the Larestan and the fall of Lar Miladi Dynasty on 1010 AH. The current paper aims at investigating the relationships between Larestan Miladi Dynasty and Shah Abbas I as well as the reasons behind the discrepancy between this local government and the central government of Safavid and its fall using a library-descriptive methodology based on the Safavid historical resources as well as the resources investigated the local history of Larestan.